Electrical responses of three classes of granule cells of the olfactory bulb to synaptic inputs in different dendritic locations - Simões-de-Souza, Fábio M.; Antunes, Gabriela; Roque, Antonio C. (Frontiers in Computational Neuroscience, 2014)
This work consists of a computational study of the electrical responses of three classes of granule cells of the olfactory bulb to synaptic activation in different dendritic locations. The constructed models were based on morphologically detailed compartmental reconstructions of three granule cell classes of the olfactory bulb with active dendrites described by Bhalla and Bower (J. Neurophysiol. 69: 1948-1965, 1993) and dendritic spine distributions described by Woolf et al. (J. Neurosci. 11: 1837-1854, 1991). The computational studies with the model neurons showed that different quantities of spines have to be activated in each dendritic region to induce an action potential, which always was originated in the active terminal dendrites, independently of the location of the stimuli and the morphology of the dendritic tree. These model predictions might have important computational implications in the context of olfactory bulb circuits.